1987
DOI: 10.3168/jds.s0022-0302(87)79991-3
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Subnormal Fertility with Copper and Magnesium Supplementation

Abstract: Two hundred and four Holstein cows and heifers were randomly assigned to mineral supplement groups 30 d prior to expected calving. Supplement treatment groups were Cu, Mg, Cu plus Mg, and no mineral supplement. The total diet of supplemented groups averaged 15 mg/kg of Cu and .30% of Mg. Pastures consisted of bermudagrass, bahiagrass, and millet during the summer and oats and ryegrass mixture during the winter. Corn and sorghum silage were also fed. Blood samples were taken just prior to initiation of mineral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

1990
1990
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 11 publications
0
6
0
4
Order By: Relevance
“…One important role of copper is being a cofactor for enzymes like the amine oxidase, copper-dependent superoxide dismutase, cytochrome oxidase, and tyrosinase. Furthermore, copper plays a critical role in female fertility (Ingraham et al, 1987). It has been reported that copper makes complexes with gonadotropin-releasing hormone (GnRH) (Michaluk and Kochman, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One important role of copper is being a cofactor for enzymes like the amine oxidase, copper-dependent superoxide dismutase, cytochrome oxidase, and tyrosinase. Furthermore, copper plays a critical role in female fertility (Ingraham et al, 1987). It has been reported that copper makes complexes with gonadotropin-releasing hormone (GnRH) (Michaluk and Kochman, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Copper supplementation was used to correct the subnormal fertility of cows (Ingraham et al, 1987). One important role of copper is being a cofactor for enzymes like the amine oxidase, copper-dependent superoxide dismutase, cytochrome oxidase, and tyrosinase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A deficiency of Mg was not expected, yet serum Mg was <0.745 mmol/L which has defined hypomagnesia in cattle (ARC 1980). Others have shown that supplemental Cu and Mg improved fertility in dairy cows even though plasma concentrations of Cu and Mg were similar among supplemented and unsupplemented groups (Ingraham et al 1987).…”
Section: Macro-and Micro-elementsmentioning
confidence: 94%
“…Muitos estudos têm relacionado nutrição a problemas de fertilidade, especialmente em vacas leiteiras que apresentam severo balanço energético negativo (BEN), evidenciado pela queda de ECC no pós-parto (Moreira, Risco et al, 2000;López-Gatius, 2003). Além disso, também tem sido demonstrado o efeito negativo do excesso de energia (Wiltbank, Lopez et al, 2006;Santos, Cerri et al, 2008), os efeitos tóxicos do nitrogênio nas dietas (Butler, 1998;Dawuda, Scaramuzzi et al, 2002;Rhoads, Rhoads et al, 2006), assim como deficiências de vitaminas e minerais (Ingraham, Kappel et al, 1987;Aréchiga, Ortíz et al, 1994;Aréchiga, Vázquez-Flores et al, 1998).…”
Section: Lista De Tabelasunclassified